PREVALENCE, ECHOGRAPHIC FEATURES OF BILIARY TRACT LESIONS IN WOMEN OF REPRODUCTIVE AGE AND PREGNANT WOMEN WITH CHRONIC VIRAL HEPATITIS "B" (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
According to WHO forecasts, in the next 10-20 years viral hepatitis will become the main problem of national health authorities, as it is expected that as a result of their spread, mortality from liver diseases may increase by 2 times, which determines the relevance of studying a different range of issues arising in connection with viral hepatitis.